(untitled) (Andamios, Revista de Investigación Social, 2011)
This essay aims to show the concept that Hobbes developed of man as an individual; such concept is structured from a dynamic link, moving constantly between the subject and the object, where the subject calls into exercise his/her powers and abilities to generate objectivity. It seeks to expose that the interest of the philosopher is the individual social experience, because his/her anthropology and epistemology lead to the social praxis of the individual whose product is the creation of the State. Hobbes lays the groundwork for a political practice that consists in setting in motion a political model embodied in the very action of the natural powers of man as an individual.